Asynchrony in Visual Consciousness and the Possible Involvement of Attention - Moutoussis, Konstantinos (Frontiers in Psychology, 2012)
When subjects are asked to perceptually bind rapidly alternating colour and motion stimuli, the pairings they report are different from the ones actually occurring in physical reality. A possible explanation for this misbinding is that the time necessary for perception is different for different visual attributes. Such an explanation is in logical harmony with the fact that the visual brain is characterized by different, functionally specialized systems, with different processing times for each; this type of organization naturally leads to different perceptual times for the corresponding attributes. In the present review, the experimental findings supporting perceptual asynchrony are presented, together with the original theoretical explanation behind the phenomenon and its implication for visual consciousness. Alternative theoretical views and additional experimental facts concerning perceptual misbinding are also reviewed, with a particular emphasis given to the role of attention. With few exceptions, most theories converge on the idea that the observed misbinding reflects a difference in perception times, which is in turn due to differences in neuronal processing times for different attributes within the brain. These processing-time differences have been attributed to several different factors, attention included, with the possibility of co-existence between them.